2023
DOI: 10.3390/ijms24032016
|View full text |Cite
|
Sign up to set email alerts
|

Actin-like Protein 6A Expression Correlates with Cancer Stem Cell-like Features and Poor Prognosis in Ovarian Cancer

Abstract: Ovarian cancer has the highest mortality rate among gynecological cancers, often diagnosed at the late stage and lacking an effective targeted therapy. Although the study of malignant features of cancer, considered to be cancer stem cells (CSCs), is emerging, the aim of this study was to predict and explore the possible mechanism and clinical value of genetic markers in the development of ovarian cancer from a combined database with CSCs features. The common differentially expressed genes (DEGs) were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Additionally, it has been reported to serve a role in tumorigenesis in head and neck squamous cell carcinoma (26) and glioma (25) by activating the Hippo/YAP pathway. In the context of ovarian cancer, high mRNA expression of ACTL6A has been reported to be associated with shortened OS (24) and platinum resistance (30). In the present study, public data demonstrated no significant association between ACTL6A mRNA expression and prognosis in patients with ovarian serous carcinoma; however, low ACTL6A protein expression levels, as detected by IHC, were associated with decreased OS.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Additionally, it has been reported to serve a role in tumorigenesis in head and neck squamous cell carcinoma (26) and glioma (25) by activating the Hippo/YAP pathway. In the context of ovarian cancer, high mRNA expression of ACTL6A has been reported to be associated with shortened OS (24) and platinum resistance (30). In the present study, public data demonstrated no significant association between ACTL6A mRNA expression and prognosis in patients with ovarian serous carcinoma; however, low ACTL6A protein expression levels, as detected by IHC, were associated with decreased OS.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have highlighted the amplification and upregulation of ACTL6A in numerous types of cancer, such as ovarian cancer, glioma, squamous cell carcinoma, osteosarcoma and hepatocellular carcinoma (24)(25)(26)(27)(28). ACTL6A has been implicated in promoting metastasis and epithelial-mesenchymal transition in hepatocellular carcinoma (28) and colon cancer (29).…”
Section: Discussionmentioning
confidence: 99%
“…ACTL6A is an ATP-dependent SWI/SNF regulatory complex protein with chromatinremodeling components (Mani et al, 2017). Recent studies revealed that follicle-stimulating hormone (FSH)-stimulated glycolysis in ovarian malignancy comprised a higher level of the poor prognostic factor ACTL6A, which forecasted metastasis and prognosis of ovarian cancer patients (Chen et al, 2023). POLR1B, which encodes DNA-directed RNA polymerase I subunit RPA2, has been linked to Treacher Collins and may be involved in cluster headaches (Harder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Its involvement in tumorigenesis across multiple cancers has been widely reported ( Meng et al, 2017 ). In particular, research conducted by Chen et al ( Chen et al, 2023 ) has established a correlation between ACTL6A expression and characteristics resembling those of cancer stem cells, highlighting its importance in the prognosis of ovarian cancer. Furthermore, ACTL6A has been associated with the inhibition of p21Cip1 promoter activity in epidermal squamous cell carcinoma, which contributes to the preservation of an aggressive phenotype ( Shrestha et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%